Rs Aggarwal 2020 2021 Solutions for Class 10 Maths Chapter 10 Trignometric Ratios are provided here with simple step-by-step explanations. These solutions for Trignometric Ratios are extremely popular among Class 10 students for Maths Trignometric Ratios Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the Rs Aggarwal 2020 2021 Book of Class 10 Maths Chapter 10 are provided here for you for free. You will also love the ad-free experience on Meritnation’s Rs Aggarwal 2020 2021 Solutions. All Rs Aggarwal 2020 2021 Solutions for class Class 10 Maths are prepared by experts and are 100% accurate.

#### Question 1:

If sin $\mathrm{\theta }=\frac{\sqrt{3}}{2}$, find the value of all T-ratios of θ.

Let us first draw a right $∆$ABC, right angled at B and $\angle C=\theta$.
Now, we know that sin $\theta$ = $\frac{\mathrm{perpendicular}}{\mathrm{hypotenuse}}$= $\frac{AB}{AC}$ = . So, if AB = $\sqrt{3}k$, then AC = 2k, where k is a positive number.
Now, using Pythagoras theorem, we have:
AC2 = AB2 + BC2
⇒ BC2 = AC2 $-$ AB2 = (2k)2 $-$ ($\sqrt{3}k$)2
⇒ BC2 = 4k2 $-$ 3k2 = k2
⇒ BC = k
Now, finding the other T-ratios using their definitions, we get:
cos $\theta$  = $\frac{BC}{AC}$ =
tan $\theta$  =

∴ cot $\theta$  = , cosec $\theta$ = and sec $\theta$  =

#### Question 2:

If cos  find the values of all T-ratios of θ.

Let us first draw a right $∆$ABC, right angled at B and .
Now, we know that cos $\theta$ = = = . So, if BC = 7k, then AC = 25k, where k is a positive number.
Now, using Pythagoras theorem, we have:
AC2 = AB2 + BC2
⇒ AB2 = AC2 $-$ BC2 = (25k)2 $-$ (7k)2.
⇒ AB2 = 625k2 $-$ 49k2 = 576k2
⇒ AB = 24k
Now, finding the other trigonometric ratios using their definitions, we get:
sin $\theta$ = =
tan $\theta$ =
∴ cot $\theta$ = , cosec $\theta$ = and sec $\theta$  =

#### Question 3:

If tan $\mathrm{\theta }=\frac{15}{8}$ find the values of all T-ratios of θ.

Let us first draw a right $∆$ABC, right angled at B and $\angle C=\theta$.
Now, we know that tan $\theta$ = $\frac{\mathrm{Perpendicular}}{\mathrm{Base}}$ = $\frac{AB}{BC}$ = $\frac{15}{8}$. So, if BC = 8k, then AB = 15k, where k is a positive number.
Now, using Pythagoras theorem, we have:
AC2 = AB2 + BC2 = (15k)2 + (8k)2
⇒ AC2 = 225k2 + 64k2 = 289k2
⇒ AC = 17k

Now, finding the other T-ratios using their definitions, we get:
sin $\theta$  = $\frac{AB}{AC}$ =
cos $\theta$  =

∴ cot $\theta$  = , cosec $\theta$ = and sec $\theta$  =

#### Question 4:

If cot θ = 2, find the value of all T-ratios of θ.

Let us first draw a right $∆$ABC, right angled at B and $\angle C=\theta$.
Now, we know that cot $\theta$$\frac{\mathrm{base}}{\mathrm{Perpendicular}}$ = $\frac{BC}{AB}$ = 2. So, if BC = 2k, then AB = k, where k is a positive number.
Now, using Pythagoras theorem, we have:
AC2 = AB2 + BC2 = (2k)2 + (k)2
⇒ AC2 = 4k2 + k2 = 5k2
⇒ AC = $\sqrt{5}$k
Now, finding the other T-ratios using their definitions, we get:
sin $\theta$  = $\frac{AB}{AC}$ =
cos $\theta$  =

∴ tan $\theta$  = , cosec $\theta$ = and sec $\theta$  =

#### Question 5:

If cosec θ = $\sqrt{10}$, the find the values of all T-ratios of θ.

Let us first draw a right $∆$ABC, right angled at B and $\angle C=\theta$.
Now, we know that cosec $\theta$ = $\frac{\mathrm{Hypotenuse}}{\mathrm{Perpendicular}}$ = $\frac{AC}{AB}$= $\frac{\sqrt{10}}{1}$. So, if AC = ($\sqrt{10}$)k, then AB = k, where k is a positive number.
Now, by using Pythagoras theorem, we have:
AC2 = AB2 + BC2
⇒ BC2 = AC2 $-$ AB2 = 10k2 $-$ k2
⇒ BC2 = 9k2
⇒ BC = 3k
Now, finding the other T-ratios using their definitions, we get:
tan $\theta$  = $\frac{AB}{BC}$ =

cos $\theta$  =

∴ , cot $\theta$  = and sec $\theta$  =

#### Question 6:

If $\mathrm{sin}\theta =\frac{{a}^{2}-{b}^{2}}{{a}^{2}+{b}^{2}}$, find the values of all T-ratios of $\theta$.

We have $\mathrm{sin}\theta =\frac{{a}^{2}-{b}^{2}}{{a}^{2}+{b}^{2}}$,

As,

${\mathrm{cos}}^{2}\theta =1-{\mathrm{sin}}^{2}\theta \phantom{\rule{0ex}{0ex}}=1-{\left(\frac{{a}^{2}-{b}^{2}}{{a}^{2}+{b}^{2}}\right)}^{2}\phantom{\rule{0ex}{0ex}}=\frac{1}{1}-\frac{{\left({a}^{2}-{b}^{2}\right)}^{2}}{{\left({a}^{2}+{b}^{2}\right)}^{2}}\phantom{\rule{0ex}{0ex}}=\frac{{\left({a}^{2}+{b}^{2}\right)}^{2}-{\left({a}^{2}-{b}^{2}\right)}^{2}}{{\left({a}^{2}+{b}^{2}\right)}^{2}}\phantom{\rule{0ex}{0ex}}=\frac{\left[\left({a}^{2}+{b}^{2}\right)-\left({a}^{2}-{b}^{2}\right)\right]\left[\left({a}^{2}+{b}^{2}\right)+\left({a}^{2}-{b}^{2}\right)\right]}{{\left({a}^{2}+{b}^{2}\right)}^{2}}$
$=\frac{\left[{a}^{2}+{b}^{2}-{a}^{2}+{b}^{2}\right]\left[{a}^{2}+{b}^{2}+{a}^{2}-{b}^{2}\right]}{{\left({a}^{2}+{b}^{2}\right)}^{2}}\phantom{\rule{0ex}{0ex}}=\frac{\left[2{b}^{2}\right]\left[2{a}^{2}\right]}{{\left({a}^{2}+{b}^{2}\right)}^{2}}\phantom{\rule{0ex}{0ex}}⇒{\mathrm{cos}}^{2}\theta =\frac{4{a}^{2}{b}^{2}}{{\left({a}^{2}+{b}^{2}\right)}^{2}}\phantom{\rule{0ex}{0ex}}⇒\mathrm{cos}\theta =\sqrt{\frac{4{a}^{2}{b}^{2}}{{\left({a}^{2}+{b}^{2}\right)}^{2}}}\phantom{\rule{0ex}{0ex}}⇒\mathrm{cos}\theta =\frac{2ab}{\left({a}^{2}+{b}^{2}\right)}$

Also,

$\mathrm{tan}\theta =\frac{\mathrm{sin}\theta }{\mathrm{cos}\theta }\phantom{\rule{0ex}{0ex}}=\frac{\left(\frac{{a}^{2}-{b}^{2}}{{a}^{2}+{b}^{2}}\right)}{\left(\frac{2ab}{{a}^{2}+{b}^{2}}\right)}\phantom{\rule{0ex}{0ex}}=\frac{{a}^{2}-{b}^{2}}{2ab}$

Now,

$\mathrm{cosec}\theta =\frac{1}{\mathrm{sin}\theta }\phantom{\rule{0ex}{0ex}}=\frac{1}{\left(\frac{{a}^{2}-{b}^{2}}{{a}^{2}+{b}^{2}}\right)}\phantom{\rule{0ex}{0ex}}=\frac{{a}^{2}+{b}^{2}}{{a}^{2}-{b}^{2}}$

Also,

$\mathrm{sec}\theta =\frac{1}{\mathrm{cos}\theta }\phantom{\rule{0ex}{0ex}}=\frac{1}{\left(\frac{2ab}{{a}^{2}+{b}^{2}}\right)}\phantom{\rule{0ex}{0ex}}=\frac{{a}^{2}+{b}^{2}}{2ab}$

And,

$\mathrm{cot}\theta =\frac{1}{\mathrm{tan}\theta }\phantom{\rule{0ex}{0ex}}=\frac{1}{\left(\frac{{a}^{2}-{b}^{2}}{2ab}\right)}\phantom{\rule{0ex}{0ex}}=\frac{2ab}{{a}^{2}-{b}^{2}}$

#### Question 7:

If $\mathrm{sin\theta }=\frac{c}{\sqrt{{c}^{2}+{d}^{2}}}$, where d > 0 then find the values of cos θ and tan θ.

#### Question 8:

If then evaluate (cos2θ – sin2θ).

#### Question 9:

If 4tan θ = 3 then prove that .

#### Question 10:

If $\mathrm{sin}\theta =\frac{a}{b}$, show that $\left(\mathrm{sec}\theta +\mathrm{tan}\theta \right)=\sqrt{\frac{b+a}{b-a}}$.

$\mathrm{LHS}=\left(\mathrm{sec}\theta +\mathrm{tan}\theta \right)\phantom{\rule{0ex}{0ex}}=\frac{1}{\mathrm{cos}\theta }+\frac{\mathrm{sin}\theta }{\mathrm{cos}\theta }\phantom{\rule{0ex}{0ex}}=\frac{1+\mathrm{sin}\theta }{\mathrm{cos}\theta }\phantom{\rule{0ex}{0ex}}=\frac{1+\mathrm{sin}\theta }{\sqrt{1-{\mathrm{sin}}^{2}\theta }}\phantom{\rule{0ex}{0ex}}=\frac{\left(1+\frac{a}{b}\right)}{\sqrt{1-{\left(\frac{a}{b}\right)}^{2}}}$
$=\frac{\left(\frac{1}{1}+\frac{a}{b}\right)}{\sqrt{\frac{1}{1}-\frac{{a}^{2}}{{b}^{2}}}}\phantom{\rule{0ex}{0ex}}=\frac{\left(\frac{b+a}{b}\right)}{\sqrt{\frac{{b}^{2}-{a}^{2}}{{b}^{2}}}}\phantom{\rule{0ex}{0ex}}=\frac{\left(\frac{b+a}{b}\right)}{\left(\frac{\sqrt{{b}^{2}-{a}^{2}}}{b}\right)}\phantom{\rule{0ex}{0ex}}=\frac{\left(b+a\right)}{\sqrt{\left(b+a\right)\left(b-a\right)}}$
$=\frac{\left(b+a\right)}{\sqrt{\left(b+a\right)}\sqrt{\left(b-a\right)}}\phantom{\rule{0ex}{0ex}}=\frac{\sqrt{\left(b+a\right)}}{\sqrt{\left(b-a\right)}}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{b+a}{b-a}}\phantom{\rule{0ex}{0ex}}=\mathrm{RHS}$

#### Question 11:

If tan θ = $\frac{a}{b}$, show that

It is given that tan .

LHS =
Dividing the numerator and denominator by cos $\theta$, we get:

(∵ tan )
Now, substituting the value of tan $\theta$ in the above expression, we get:

i.e., LHS = RHS

Hence proved.

#### Question 12:

If then evaluate .

If then evaluate

#### Question 14:

If $\mathrm{sin}\alpha =\frac{1}{2}$, prove that $\left(3\mathrm{cos}\alpha -4{\mathrm{cos}}^{3}\alpha \right)=0$.

$\mathrm{LHS}=\left(3\mathrm{cos}\alpha -4{\mathrm{cos}}^{3}\alpha \right)\phantom{\rule{0ex}{0ex}}=\mathrm{cos}\alpha \left(3-4{\mathrm{cos}}^{2}\alpha \right)\phantom{\rule{0ex}{0ex}}=\sqrt{1-{\mathrm{sin}}^{2}\alpha }\left[3-4\left(1-{\mathrm{sin}}^{2}\alpha \right)\right]\phantom{\rule{0ex}{0ex}}=\sqrt{1-{\left(\frac{1}{2}\right)}^{2}}\left[3-4\left(1-{\left(\frac{1}{2}\right)}^{2}\right)\right]\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{1}{1}-\frac{1}{4}}\left[3-4\left(\frac{1}{1}-\frac{1}{4}\right)\right]\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{3}{4}}\left[3-4\left(\frac{3}{4}\right)\right]\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{3}{4}}\left[3-3\right]\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{3}{4}}\left[0\right]\phantom{\rule{0ex}{0ex}}=0\phantom{\rule{0ex}{0ex}}=\mathrm{RHS}$

#### Question 15:

If 3 cot θ = 2, show that $\left(\frac{4\mathrm{sin\theta }-3\mathrm{cos\theta }}{2\mathrm{sin\theta }+6\mathrm{cos\theta }}\right)=\frac{1}{3}.$

It is given that cot .

LHS  =
Dividing the above expression by sin $\theta$, we get:
[∵ cot ]
Now, substituting the values of cot $\theta$ in the above expression, we get:

i.e., LHS = RHS

Hence proved.

#### Question 16:

If sec θ = $\frac{17}{8}$ then prove that $\frac{3-4{\mathrm{sin}}^{2}\mathrm{\theta }}{4{\mathrm{cos}}^{2}\mathrm{\theta }-3}=\frac{3-{\mathrm{tan}}^{2}\mathrm{\theta }}{1-3{\mathrm{tan}}^{2}\mathrm{\theta }}$.

It is given that sec $\theta$ = $\frac{17}{8}$.

Let us consider a right $△$ABC right angled at B and $\angle C=\theta$.
We know that cos $\theta$ = So, if BC = 8k, then AC = 17k, where k is a positive number.
Using Pythagoras theorem, we have:
AC2 = AB2 + BC2
⇒ AB2 = AC2 $-$ BC2 = (17k)2 $-$ (8k)2
⇒ AB2 = 289k2 $-$ 64k2 = 225k2
⇒ AB = 15k.

Now, tan $\theta$  = and sin $\theta$ =

The given expression is .

Substituting the values in the above expression, we get:

∴ LHS = RHS
Hence proved.

#### Question 17:

If tan θ = $\frac{20}{21}$, show that$\frac{\left(1-\mathrm{sin\theta }+\mathrm{cos\theta }\right)}{\left(1+\mathrm{sin\theta }+\mathrm{cos\theta }\right)}=\frac{3}{7}.$

Let us consider a right $△$ABC right angled at B and $\angle C=\theta$.
Now, we know that tan $\theta$$\frac{AB}{BC}$ = $\frac{20}{21}$ So, if AB = 20k, then BC = 21k, where k is a positive number.
Using Pythagoras theorem, we get:
AC2 = AB2 + BC2
⇒ AC2= (20k)2 + (21k)2
⇒ AC2 = 841k2
⇒  AC = 29k
Now, sin $\theta$ = and cos $\theta$ =

Substituting these values in the given expression, we get:

∴ LHS = RHS

Hence proved.

#### Question 18:

If tan θ = $\frac{1}{\sqrt{7}}$ then prove that $\left(\frac{{\mathrm{cosec}}^{2}\mathrm{\theta }+{\mathrm{sec}}^{2}\mathrm{\theta }}{{\mathrm{cosec}}^{2}\mathrm{\theta }-{\mathrm{sec}}^{2}\mathrm{\theta }}\right)=\frac{4}{3}.$

Let us consider a right $△$ABC, right angled at B and $\angle C=\theta$.
Now it is given that tan $\theta$$\frac{AB}{BC}$$\frac{1}{\sqrt{7}}$. So, if AB = k, then BC = $\sqrt{7}$k, where k is a positive number.
Using Pythagoras theorem, we have:
AC2 = AB2 + BC2
⇒ AC2 = (k)2 + ($\sqrt{7}$k)2
⇒ AC2 = k2 + 7k2
⇒ AC = 2$\sqrt{2}$k
Now, finding out the values of the other trigonometric ratios, we have:
sin $\theta$  =
cos $\theta$  =
∴ cosec $\theta$  = and sec $\theta$   =
Substituting the values of cosec $\theta$  and sec $\theta$  in the given expression, we get:

i.e., LHS = RHS

Hence proved.

#### Question 19:

If $\mathrm{sin}\theta =\frac{3}{4}$, show that $\sqrt{\frac{{\mathrm{cosec}}^{2}\theta -{\mathrm{cot}}^{2}\theta }{{\mathrm{sec}}^{2}\theta -1}}=\frac{\sqrt{7}}{3}$.

$\mathrm{LHS}=\sqrt{\frac{{\mathrm{cosec}}^{2}\theta -{\mathrm{cot}}^{2}\theta }{{\mathrm{sec}}^{2}\theta -1}}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{1}{{\mathrm{tan}}^{2}\theta }}\phantom{\rule{0ex}{0ex}}=\sqrt{{\mathrm{cot}}^{2}\theta }\phantom{\rule{0ex}{0ex}}=\mathrm{cot}\theta \phantom{\rule{0ex}{0ex}}=\sqrt{{\mathrm{cosec}}^{2}\theta -1}\phantom{\rule{0ex}{0ex}}=\sqrt{{\left(\frac{1}{\mathrm{sin}\theta }\right)}^{2}-1}\phantom{\rule{0ex}{0ex}}=\sqrt{{\left(\frac{1}{\left(\frac{3}{4}\right)}\right)}^{2}-1}\phantom{\rule{0ex}{0ex}}=\sqrt{{\left(\frac{4}{3}\right)}^{2}-1}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{16}{9}-1}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{16-9}{9}}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{7}{9}}\phantom{\rule{0ex}{0ex}}=\frac{\sqrt{7}}{3}\phantom{\rule{0ex}{0ex}}=\mathrm{RHS}$

#### Question 20:

If 3 tan A = 4 then prove that
(i)
(ii)

(i)
​
$=\sqrt{\frac{\left(\frac{1}{4}\right)}{\left(\frac{7}{4}\right)}}\phantom{\rule{0ex}{0ex}}=\sqrt{\frac{1}{7}}\phantom{\rule{0ex}{0ex}}=\frac{1}{\sqrt{7}}\phantom{\rule{0ex}{0ex}}=\mathrm{RHS}$

(ii)

If .

#### Question 22:

In a right $∆\mathrm{ABC}$, right-angled at $\mathrm{B}$, if $\mathrm{tanA}=1$, then verify that $2\mathrm{sinA}·\mathrm{cosA}=1$.

#### Question 23:

In the given figure, ABCD is a rectangle in which diag. AC = 17 cm, ∠BCA = θ and .
Find (i) the area of rect. ABCD, (ii) the perimeter of rect. ABCD. #### Question 24:

If $x=\mathrm{cosecA}+\mathrm{cosA}$ and $y=\mathrm{cosecA}-\mathrm{cosA}$, then prove that ${\left(\frac{2}{x+y}\right)}^{2}+{\left(\frac{x-y}{2}\right)}^{2}-1=0$.

$\mathrm{LHS}={\left(\frac{2}{x+y}\right)}^{2}+{\left(\frac{x-y}{2}\right)}^{2}-1\phantom{\rule{0ex}{0ex}}={\left[\frac{2}{\left(\mathrm{cosecA}+\mathrm{cosA}\right)+\left(\mathrm{cosecA}-\mathrm{cosA}\right)}\right]}^{2}+{\left[\frac{\left(\mathrm{cosecA}+\mathrm{cosA}\right)-\left(\mathrm{cosecA}-\mathrm{cosA}\right)}{2}\right]}^{2}-1\phantom{\rule{0ex}{0ex}}={\left[\frac{2}{\mathrm{cosecA}+\mathrm{cosA}+\mathrm{cosecA}-\mathrm{cosA}}\right]}^{2}+{\left[\frac{\mathrm{cosecA}+\mathrm{cosA}-\mathrm{cosecA}+\mathrm{cosA}}{2}\right]}^{2}-1\phantom{\rule{0ex}{0ex}}={\left[\frac{2}{2\mathrm{cosecA}}\right]}^{2}+{\left[\frac{2\mathrm{cosA}}{2}\right]}^{2}-1$
$={\left[\frac{1}{\mathrm{cosecA}}\right]}^{2}+{\left[\mathrm{cosA}\right]}^{2}-1\phantom{\rule{0ex}{0ex}}={\left[\mathrm{sinA}\right]}^{2}+{\left[\mathrm{cosA}\right]}^{2}-1\phantom{\rule{0ex}{0ex}}={\mathrm{sin}}^{2}\mathrm{A}+{\mathrm{cos}}^{2}\mathrm{A}-1\phantom{\rule{0ex}{0ex}}=1-1\phantom{\rule{0ex}{0ex}}=0\phantom{\rule{0ex}{0ex}}=\mathrm{RHS}$

#### Question 25:

If $x=\mathrm{cotA}+\mathrm{cosA}$ and $y=\mathrm{cotA}-\mathrm{cosA}$, prove that ${\left(\frac{x-y}{x+y}\right)}^{2}+{\left(\frac{x-y}{2}\right)}^{2}=1$.

#### Question 26:

In the figure of . Find  In ,

Using Pythagoras theorem, we get

$\mathrm{PQ}=\sqrt{{\mathrm{PR}}^{2}-{\mathrm{QR}}^{2}}\phantom{\rule{0ex}{0ex}}=\sqrt{{\left(x+2\right)}^{2}-{x}^{2}}\phantom{\rule{0ex}{0ex}}=\sqrt{{x}^{2}+4x+4-{x}^{2}}\phantom{\rule{0ex}{0ex}}=\sqrt{4\left(x+1\right)}\phantom{\rule{0ex}{0ex}}=2\sqrt{x+1}$

Now,

#### Question 27:

If , find the value of $\left({\mathrm{cot}}^{2}A+\frac{1}{{\mathrm{cot}}^{2}A}\right)$.

#### Question 28:

If , find the value of sin θ.

#### Question 29:

If $\angle$A and $\angle$B are acute angles such that sinA = sinB, then prove that $\angle$A = $\angle$B. In $∆$ABC, $\angle$C = 90$°$
sinA = $\frac{\mathrm{BC}}{\mathrm{AB}}$ and
sinB = $\frac{\mathrm{AC}}{\mathrm{AB}}$

As, sinA = sinB
$⇒$$\frac{\mathrm{BC}}{\mathrm{AB}}$ = $\frac{\mathrm{AC}}{\mathrm{AB}}$
$⇒$BC = AC
So, $\angle$A = $\angle$B             (Angles opposite to equal sides are equal)

#### Question 30:

If $\angle \mathrm{A}$ and $\angle \mathrm{B}$ are acute angles such that tanA = tanB, the prove that $\angle \mathrm{A}=\angle \mathrm{B}$. In ,

#### Question 1:

If
(a) $\frac{15}{17}$

(b) $\frac{17}{15}$

(c) $\frac{17}{8}$

(d) $\frac{8}{17}$

Hence, the correct option is (c).

#### Question 2:

If = ?

(a) 2

(b) $\frac{1}{2}$

(c) $\frac{\sqrt{3}}{2}$

(d) $\frac{2}{\sqrt{3}}$

Hence, the correct option is (a).

#### Question 3:

If

(a) $\frac{1}{\sqrt{1}0}$

(b) $\frac{2}{\sqrt{10}}$

(c) $\frac{3}{\sqrt{10}}$

(d) $\frac{\sqrt{10}}{3}$

Hence, the correct option is (d).

#### Question 4:

If

(a) $\frac{7}{25}$

(b) $\frac{24}{25}$

(c) $\frac{7}{24}$

(d) $\frac{24}{7}$

Hence, the correct option is (b).

#### Question 5:

If
(a) $\frac{\sqrt{3}}{2}$

(b) 1

(c) $\sqrt{3}$

(d) $\frac{1}{\sqrt{3}}$

Hence, the correct option is (c).

#### Question 6:

If
(a) $\frac{3}{4}$

(b) $\frac{4}{3}$

(c) $\frac{3}{5}$

(d) $\frac{5}{3}$

Hence, the correct option is (a).

#### Question 7:

If
(a) $\frac{7}{3}$

(b) $\frac{7}{4}$

(c) $\frac{7}{5}$

(d) $\frac{5}{7}$

Hence, the correct option is (c).

#### Question 8:

If (tan θ + cot θ) = 5 then (tan2 θ + cot2 θ) = ?
(a) 27
(b) 25
(c) 24
(d) 23

#### Question 9:

If (cos θ + sec θ) = $\frac{5}{2}$ then (cos2 θ + sec2 θ) = ?
(a) $\frac{17}{4}$

(b) $\frac{21}{4}$

(c) $\frac{29}{4}$

(d) $\frac{33}{4}$

#### Question 10:

If 4tan θ = 3 then (cos2 θ – sin2 θ) = ?
(a) $\frac{4}{25}$

(b) $\frac{7}{25}$

(c) 1

(d) $\frac{11}{25}$

#### Question 11:

If
(a) $\frac{3}{7}$

(b) $\frac{2}{7}$

(c) $\frac{1}{7}$

(d) 0

#### Question 12:

If 3cos θ = 2 then (2sec2 θ + 2tan2 θ – 7) = ?
(a) 0
(b) 1
(c) 3
(4) 4

#### Question 13:

If sec θ + tan θ + 1 = 0 then (sec θ – tan θ) = ?
(a) 1
(b) –1
(c) 0
(d) 2

#### Question 14:

If cos A + cos2 A = 1 then (sin2 A + sin4 A) = ?
(a) $\frac{1}{2}$

(b) 2

(c) 1

(d) 4

#### Question 15:

If

(a) $\left(2+\sqrt{3}\right)$

(b) $2\sqrt{3}$

(c) $\sqrt{2}$

(d) $\sqrt{3}$

#### Question 16:

If $\sqrt{3}$ tan θ = 3sin θ then (sin2θ – cos2θ) = ?

(a) $\frac{1}{3}$

(b) $\frac{1}{\sqrt{3}}$

(c) $\sqrt{3}$

(d) $\frac{2}{\sqrt{3}}$